Athletic Footwear and Orthoses in Sports Medicine - Werd, Matthew B.; Knight, E. Leslie; Langer, Paul R. (Springer International Publishing : Imprint: Springer, 2017)
Now in a revised and expanded second edition, including an expanded section on running footwear and additional sports-specific recommendations, this updated, practical resource provides a concise and logical approach to prescribing footwear that will maximize performance and minimize injury in athletes. From fundamentals - including athletic foot types, basic biomechanics and gait evaluation - to step-by-step guidance through assessment and prescription of shoes, socks, lacing, inserts, and orthoses, this book is both comprehensive and easily accessible. A new section has been added to cover the array of different considerations for running footwear (barefoot, minimalist, maximalist), as well as new sport-specific recommendations. As in the previous edition, referral, coding and billing are also addressed. Photographs and drawings clearly illustrate key concepts, and wherever relevant, the authors have incorporated evidence-based medicine. By presenting new and updated essential information in a user-friendly format, Athletic Footwear and Orthoses in Sports Medicine, Second Edition will prove to be invaluable for sports medicine physicians, podiatrists, orthopedists, physical therapists, and athletic trainers.
Keywords: Medicine.; Orthopedics.; Primary care (Medicine).; Sports medicine.; elektronické knihy; electronic books